Total Laparoscopic Hysterectomy: Our 5-Year Experience (1998–2002) - Bonilla, David J. (the Academic Division of Ochsner Clinic Foundation, 2010)
PURPOSE: To review our experience performing total laparoscopic hysterectomy since we first introduced this procedure in 1998. METHODS: A retrospective cohort study was performed for patients undergoing total laparoscopic hysterectomy at Ochsner Clinic Foundation from February 1998 through December 2002. Rates of complications, successful completion, length of hospital stay, readmission, and reoperation were determined for this period. RESULTS: Among 511 patients who underwent attempted total laparoscopic hysterectomy, 487 procedures (95.3%) were completed by laparoscopy. The major intraoperative complication rate was 3.9%, and the major postoperative complication rate was 4.7%. No significant differences were seen in the intraoperative and postoperative complication rates of patients who were morbidly obese (body mass index ≥30 kg/m(2)), patients with enlarged uteri (≥300 g), or patients who underwent concomitant procedures (unilateral or bilateral salpingo-oophorectomy and lysis of adhesions). The readmission rate was 4.1%, and the reoperation rate was 2%. None of the variables studied, including age, medical problems, morbid obesity, concomitant procedures, or enlarged uterus, were found to have an association with readmission or reoperation rates. CONCLUSIONS: Total laparoscopic hysterectomy can be performed successfully in most patients with benign indications. Morbidity is comparable to that of other types of hysterectomies, and this technique may be a more reasonable approach under some circumstances.